The automotive industry and the environment : a technical, business and social future - Nieuwenhuis, Paul (Woodhead Publishing in environmental management., 2003)
The future of car manufacturing may be very different to the current practice of large scale, large assembly plant construction methods, based on economies of scale and marketing new vehicles with offering ever increasing complexity and value-added options. A sustainable future is envisaged in this ground-breaking study which concentrates on the recent research into alternative production methods with an emphasis on life-cycle management, recyclability and manufacture tailored to customer's individual specifications.